Dwa ksiezyce - Kuncewiczowa, Maria Szczepanska, 1897- (Lublin : Wydawn. Lubelskie, 1989)
The story is set in Kazimierz-on-the-Vistula, and the backdrop is the people, the landscape and the architecture of the historic town.
Keywords: Kazimierz (Krakow, Poland) -- Fiction